Women's studies encyclopedia - Tierney, Helen (Greenwood Electronic Media, 1999)
A multidisciplinary reference on the collective experiences of women. Prepared by 425 scholars from all disciplines, features 701 alphabetically listed entries, coverage of 1,250 historical figures, analysis of women and society and culture throughout history, cross-references, and bibliography.